Atuação dos agentes de informação na fronteira sul-rio-grandense nos séculos XVIII e XIX: Agents of information operation in the sul-rio-grandense frontier in the XVIII e XIX centuries (Revista de História da UEG (REVHIST), 2019)
Abstract: We treat about the frontier region between the two Iberian crowns, in the XVIII and XIX centuries. Region that was plentiful permeable for years, what allowed various shapes of interaction and acquaintanceship between the both side groups. Therefore, we seek to connect distinguish aspects, assembling the characteristics of region and frontier, to the very history of the sul-riograndense frontier. Encompassing important aspects, for the comprehension of the Rio-grandense’s autonomy in this frontier region. As well, the maintenance of the Guerra dos Farrapos, that begun in the 1835 and lasting to 1845, being this event, the principal armed conflict in the Provincial of Rio Grande de São Pedro, that was created in 28 February 1821. However, the principal focus of this paper is the information agents in the region between the XVIII and XIX centuries.Keywords: Frontier. Agents of Information. Guerra dos Farrapos.